Industrial policy and Caribbean development - Pantin, Dennis (UWI St. AugustineTT, 1995)
Assesses the current economic context for industrial policy in CARICOM, in particular the policy conditionalities of the multilateral institutions. Provides a critical review of the theoretical and empirical feasibility of industrial policy in a Caribbean-specific case.